Maternal and Pediatric Health Outcomes in relation to Gestational Vitamin D Sufficiency - Stephen J. Genuis (Obstetrics and Gynecology International)
Juxtaposed with monumental improvement in maternal-fetal outcomes over the last century, there has been the recent emergence of rising rates of gestational complications including preterm birth, operative delivery, and gestational diabetes. At the same time, there has been a burgeoning problem with widespread vitamin D deficiency among populations of many developed nations. This paper provides a brief review of potential health outcomes recently linked to gestational vitamin D deficiency, including preterm birth, cesarean delivery, and gestational diabetes. Although immediate costs for obstetric complications related to gestational vitamin D insufficiency may be modest, the short- and long-term costs for pediatric healthcare resulting from such gestational complications may be enormous and present an enduring burden on healthcare systems. With increasing evidence pointing to fetal origins of some later life disease, securing vitamin D sufficiency in pregnancy appears to be a simple, safe, and cost-effective measure that can be incorporated into routine preconception and prenatal care in the offices of primary care clinicians. Education on gestational nutritional requirements should be a fundamental part of medical education and residency training, instruction that has been sorely lacking to date.